Unique amorphous/crystalline heterophase coupling for an efficient oxygen evolution reaction. Issue 48 (30th November 2022) - Bai, Sitian; Mou, Yiwei; Wan, Jin; Wang, Yanwei; Li, Weibo; Zhang, Huijuan; Luo, Ping; Wang, Yu
Abstract : Designing amorphous/crystalline heterophase catalysts is still in the initial stage, and the study of amorphous/crystalline heterophase and carbon-free catalysts has not yet been realized. Abstract : Designing amorphous/crystalline heterophase catalysts is still in the initial stage, and the study of amorphous/crystalline heterophase and carbon-free catalysts has not yet been realized. Herein, we report a unique amorphous/crystalline heterophase catalyst consisting of NiFe alloy nanoparticles (NPs) supported on Ti4 O7 (NiFe/Ti4 O7 ) for the first time, which is achieved by a heterophase supporting strategy of dual heat treatment. Surprisingly, the amorphous/crystalline heterophase is flexibly composed of amorphous and crystalline phases of alloy NPs and Ti4 O7 . The heterophase coupling endows the catalyst with a low overpotential (256 mV at 10 mA cm −2 ), a small Tafel slope (47 mV dec −1 ) and excellent endurance stability (over 100 h) in 1 M KOH electrolyte, which already outperforms commercial RuO2 (338 mV and 113 mV dec −1 ) and exceeds most reported representative carbon-based and titanium-based non-precious metal catalysts. The density functional theory (DFT) calculations and experimental results reveal that the unique amorphous/crystalline heterophase coupling in NiFe/Ti4 O7 results in electron transfer between the alloy NPs and Ti4 O7, allowing more catalytically active sites and faster interfacial electron transfer dynamics. This work provides insights into the synthesis of amorphous/crystalline heterophase catalysts and can be generalized to the heterophase coupling of other transition metal-based electrocatalysts.